Molluscicidal activities of curcumin-nisin polylactic acid nanoparticle on Biomphalaria pfeifferi. - Michael E Omobhude; Olajumoke A Morenikeji; Oyetunde T Oyeyemi (Public Library of Science (PLoS), 2017)
BACKGROUND:Snail intermediate host control is a widely canvassed strategy for schistosomiasis control in endemic countries. While there have been increasing studies on the search for potent molluscicides in the past years, the use of nanoparticulate agents as molluscicides is yet to gain wide attention. The aim of this study was to assess the molluscicidal potential of curcumin-nisin poly lactic acid (PLA) entrapped nanoparticle (CurNisNp) against Biomphalaria pfeifferi, a snail intermediate host for Schistosoma mansoni. METHODOLOGY/PRINCIPAL FINDINGS:CurNisNp formulated by double emulsion method was tested against the young adults, < 1 week, 1-2-week old juveniles, 1 day (blastula) and 7 day-old (hippo-stage) egg masses of B. pfeifferi. Mortality in the different stages was determined after 96-h of exposure at varying concentrations (350, 175, 87.5, 43.75 and 21.88 ppm). The sub-lethal effects of CurNisNp on the hatchability of the 7-day-old egg masses and egg laying capacity of the young adult snails were determined. The CurNisNp diameter, polydispersity index (PDI), zeta potential and drug entrapment efficiency were 284.0 ± 17.9 nm, 0.166 ± 0.03, -16.6 ± 2.45 mV and 35.0% respectively. The < 1 week old juveniles and the 1-day-old egg stage (blastula) of B. pfeifferi with LC50 277.9 ppm and 4279.5 ppm were the most susceptible and resistant stages to the drug respectively. CurNisNp was also observed to cause significant reductions (P<0.05) in egg hatchability and egg laying capacity with strong negative correlation between egg laying capacity and concentration (r = -0.928; P<0.05). CONCLUSION/SIGNIFICANCE:This study showed that CurNisNp has molluscicidal activities on different developmental stages of B. pfeifferi. It is therefore recommended that the formulation be more optimised to give a nanoparticle with a narrow range monodispersed PDI for better drug distribution and eventual greater molluscicidal activities.